Educação ambiental nos anos finais do ensino fundamental em uma escola do campo: uma análise a partir do projeto político pedagógico - Lopes, Talita Mazzini [UNESP]; Zancul, Maria Cristina de Senzi [UNESP] (My University, 2012)
Environmental education (EE), a critical component to face the environmental crisis, must be present in formal education in a continuous, permanent and transversal way. Studies show, however, that EE occurs, often, in a sporadic and discontinuous way, and that it is mainly linked to Sciences. The objective of this study was to investigate the inclusion of environmental subjects in the Political Pedagogical Project (PPP) of a rural school, in Araraquara, SP. Through documentary analysis of the PPP, proposals for the Environmental Education for the last years of elementary education were examined. The results allowed the understanding, in a complex and contextualized way, of aspects related to the presence of environmental subjects in the school curriculum. They reveal that the suggestion of working with Environment attend the recommendations of the conference of Tbilisi and of Brazilian National Curriculum (PCN).

A Educação Ambiental (EA), elemento crítico para o enfrentamento da crise ambiental, deve estar presente na educação formal de maneira contínua, permanente e transversal. Pesquisas apontam, no entanto, que o trabalho com a EA ocorre, muitas vezes, de maneira esporádica e descontínua e está vinculado, principalmente, à disciplina Ciências. O objetivo deste estudo foi investigar como se dá a inserção da temática ambiental no Projeto Político Pedagógico (PPP) de uma escola do campo, do município de Araraquara-SP. Por meio da análise documental do PPP foram examinadas as propostas referentes à Educação Ambiental para os anos finais do ensino fundamental. Os resultados permitiram compreender, de forma complexa e contextualizada, aspectos relevantes da inserção da temática ambiental no currículo escolar e revelam que as sugestões para os trabalhos com o tema Meio Ambiente, atendem, em linhas gerais às recomendações da conferência de Tblisi e às orientações dos Parâmetros Curriculares Nacionais (PCN).
Environmental education in the last years of elementary education in a rural school: an analysis from the political pedagogical project
Keywords: Environmental education; pedagogical practices; elementary education; political pedagogical project; Educação ambiental; práticas pedagógicas; ensino fundamental; projeto político pedagógico